2007
DOI: 10.2105/ajph.2006.093526
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Mandatory HIV Testing During Pregnancy in Areas With High HIV Prevalence Rates: Ethical and Policy Issues

Abstract: We analyzed the ethical and policy issues surrounding mandatory HIV testing of pregnant women in areas with high HIV prevalence rates. Through this analysis, we seek to demonstrate that a mandatory approach to testing and treatment has the potential to significantly reduce perinatal transmission of HIV and defend the view that mandatory testing is morally required if a number of conditions can be met. If such programs are to be introduced, continuing medical care, including highly active antiretroviral therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…By implementing this Mandatory HIV testing strategy and ensuring prompt treatment there is a great potential to reduce the perinatal transmission of HIV from mother to child (this again depends on the prevalence rate and the number of lives saved through testing & prompt initiation of Zidovudine [2] therapy etc.). To support one opinion where mandatory HIV testing is required on moral grounds, there are definitely certain prerequisite conditions (e.g.…”
Section: Arguments That Support Voice For Mandatory Testing Among Prementioning
confidence: 99%
“…By implementing this Mandatory HIV testing strategy and ensuring prompt treatment there is a great potential to reduce the perinatal transmission of HIV from mother to child (this again depends on the prevalence rate and the number of lives saved through testing & prompt initiation of Zidovudine [2] therapy etc.). To support one opinion where mandatory HIV testing is required on moral grounds, there are definitely certain prerequisite conditions (e.g.…”
Section: Arguments That Support Voice For Mandatory Testing Among Prementioning
confidence: 99%
“…However, where resources are available and the HIV prevalence is high, the argument favors HIV testing. Under such conditions, some authors reported that it is ethically plausible to institute mandatory HIV testing [10,11]. However, the denial of opportunity to consent to an HIV test directly infringes on individual right of autonomy and dignity and can affect utilization of healthcare services.…”
Section: Ethical Considerations Around Hiv Testing For Pregnant Womenmentioning
confidence: 99%
“…In 2006, Clark called for mandatory HIV testing in Botswana where HIV prevalence rates are the highest in the African continent [10]. Schuklenk and Kleinsmidt, in 2007, proposed to pilot mandatory HIV testing of pregnant women during antenatal care in areas with high HIV prevalence rates [11]. While mandatory testing is ethically plausible, particularly when coupled with guaranteed access to treatment and care, the moment to employ this strategy is yet to come [16].…”
Section: Mandatory Hiv Testing During Pregnancymentioning
confidence: 99%
“…Some authors have concluded that prevention outweighs the possible violation of the pregnant woman's right to privacy [13], whereas others argue in favour of mandatory testing and treatment contingent on a number of conditions being met: the woman has voluntarily chosen to carry the fetus to term, she has had a reasonable alternative course of action made available (termination) and continued treatment with HAART is available to her [14].…”
Section: Recent Findingsmentioning
confidence: 99%